Educação em saúde : revisitando as experiências do Hospital Universitário Lauro Wanderley - Paraíba - Brasil - Serápio, Sheila Duarte da Silva (2024)
With the expansion of hospital classes, especially at the end of the 1980s, with the promulgation of the 1988 Constitution and later in the 1990s with the Child and Adolescent Statute and the Education Guidelines and Bases Law, it was of these documents, the right to education was guaranteed for all and, later with Law No. 13,716, of September 24, 2018, access to education was guaranteed for students undergoing medical treatment, a law that changed the Guidelines Law and Bases of National Education (LDB) nº 9,394, of December 20, 1996. Given the emergence of laws and studies, research became more noticeable and these sought to encourage ideas and thoughts, presenting the difficulties encountered and the evolutions evidenced, in the quest to try to establish a connection with the practice or modify/improve it. Therefore, studies developed in the area of education and health are of fundamental importance, as they give visibility to a right that is so little known, within this new field of professional activity for the pedagogue, which is the right to education. However, health and education are considered rights related to equality, as they guarantee individuals the material conditions necessary for their dignified survival, thus considering them essential for the full practice of citizenship as they are considered social rights. The Study is an integrative review of qualitative research developed at the Lauro Wardeley University Hospital on education from 2013 to 2022, based on the method of Whittemore and Knafl (2005), carefully following the following steps: formulation and identification of the problem, data collection, data evaluation, data analysis and interpretation, and data presentation. The general objective of this research is to analyze the different scientific contributions regarding hospital classes at the Lauro Wanderley University Hospital in the light of public policies in the area of education, characterizing the common themes and subjects covered. To this end, this objective unfolds with the following specific objectives: Verify what was produced about pedagogical experiences at the Lauro Wanderley University Hospital; Identify common and divergent themes between the research analyzed; Search for possible relationships between the research studied and public policies on the legality of pedagogical experiences in hospitals or at home. The presentation of this dissertation is expected to contribute significantly to the discussion of this topic, even with so few publications.